The Edinburgh companion to Scots - Corbett, John, 1959-; McClure, J. Derrick, 1944-; Stuart-Smith, Jane, 1965- (Edinburgh University Press, 2003)
The Edinburgh Companion to Scots is a comprehensive introduction to the study of older and present-day Scots language. The aim of the volume is to explain and illustrate methods of research into Scots and Scottish English. Topics include the grammar, vocabulary and pronunciation of contemporary speech in Scotland, and the investigation of Older Scots written texts. There is further coverage of issues such as modern literary Scots, language planning, placenames and personal names, and the development of Scots overseas. Each chapter gives a brief overview of the topic, and provides case studies to illustrate avenues of exploration for those beginning to develop research techniques. The book is designed as an accessible introduction to key issues and methods of investigation for undergraduate students interested in the way language has developed in Scotland.